Thermal convection in Al2O3–water nanoliquid rotating chamber with a local isothermal heater. (June 2019) - Mikhailenko, S.A.; Sheremet, M.A.; Oztop, H.F.; Abu-Hamdeh, Nidal
Highlights: Computational modeling of convective thermal transport and liquid circulation within a rotating enclosure loaded with water-based nanoliquid is performed. Mathematical model formulated using the dimensionless non-primitive parameters has been worked out by the finite difference technique. Investigation has been performed in a wide range of the Rayleigh number, Taylor number and nanoparticles volume fraction. Addition of nanoparticles in the case of rotationless and low Taylor numbers diminishes the average Nusselt number. Abstract: Convective energy transport within rotating cavities is a very important topic taking into account different rotating systems in electronics, chemical industry and thermal engineering. This study is consecrated to computational modeling of convective thermal transport and liquid circulation within a rotating enclosure loaded with water-based nanoliquid. Mathematical model formulated using the dimensionless non-primitive parameters has been worked out by the finite difference technique. The developed computational code has been verified using experimental and theoretical data of other researchers. Investigation has been performed in a broad range of the Rayleigh number, Taylor number and nanoparticles volume fraction. Calculated data have indicated the energy transport enhancement with nanoparticles concentration for high Taylor numbers. Graphical abstract: Image, graphical abstract